2016
DOI: 10.1016/j.jml.2016.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Giving and stealing ideas in memory: Source errors in recall are influenced by both early-selection and late-correction retrieval processes

Abstract: Previous studies of unconscious plagiarism have asked participants to recall their own ideas from a previous group-problem solving session, and have typically reported that people mistakenly include a partner's responses when trying to recall their own. To date, there has been little research looking at the propensity to include one's own responses when trying to recall a partner's previous contribution to the group. Experiment 1 demonstrated that people make both kinds of source-error during recall, but sourc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 43 publications
3
11
0
Order By: Relevance
“…However, there was no interaction between Task and Data type, F (1,33) = 1.03, MSe = 10.80, p = 0.32, = 0.030. In subsequent step-down analyses, we tested whether observed source errors were greater than predicted in each of the two retrieval tasks, that is, whether both the “donating” and “stealing” effects was observed ( Perfect et al, 2009 ; Hollins et al, 2016a , b ). Indeed, observed frequencies surpassed predicted frequencies in the Recall own task, t (17) = 3.92, p < 0.001, d av = 1.28 and in the Recall partner task, t (16) = 1.84, p = 0.042, d av = 0.59, both one-tailed.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there was no interaction between Task and Data type, F (1,33) = 1.03, MSe = 10.80, p = 0.32, = 0.030. In subsequent step-down analyses, we tested whether observed source errors were greater than predicted in each of the two retrieval tasks, that is, whether both the “donating” and “stealing” effects was observed ( Perfect et al, 2009 ; Hollins et al, 2016a , b ). Indeed, observed frequencies surpassed predicted frequencies in the Recall own task, t (17) = 3.92, p < 0.001, d av = 1.28 and in the Recall partner task, t (16) = 1.84, p = 0.042, d av = 0.59, both one-tailed.…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, recent work has shown that people do not only “steal” their partner’s ideas, but also “donate” their own ideas. In Hollins et al (2016a) , participants alternated generating solutions to verbal fluency problems. Subsequently, when asked to recall their own ideas, participants showed the well-known unconscious plagiarism effect and included solutions generated by their partner.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unconscious plagiarism may occur when individuals make mistakes distinguishing their response from the response of others due to psychological errors involved in source recall (Hollins et al 2016). Authors may also be susceptible to unintentional plagiarism if work schedule demands and disorganized records coincide to confuse sources of information (Nicholls, 2014).…”
mentioning
confidence: 99%
“…Most people, though, share the intuition that they will be able to remember the source of information that they have just encountered. Here we explore errors that challenge this intuition, demonstrating frequent source errors for information that was attended and used to perform a task moments before.The phenomenon of failing to remember the source of retrievable information has been variously labeled as source amnesia, source forgetting, source monitoring errors, source misattributions, source errors and so on (Mitchell & Johnson, 2009) and has been extensively studied (e.g., Glisky, Polster, & Routhieaux, 1995;Johnson, Hashtroudi, & Lindsay, 1993;Hollins, Lange, Berry, & Dennis, 2016;Maillet, & Rajah, 2016;Mitchell & Johnson, 2009;Mitchell, Johnson, Raye, & Greene, 2004;2006;Wilding & Rugg, 1996). Source memory is broadly defined as remembered information that specifies how an event was experienced, such as perceptual (e.g., col or, format of a stimulus), spatial-temporal, and affective details (Glisky et al, 1995;Johnson, et al, 1993).…”
mentioning
confidence: 99%